Zika virus infections from the perspective of the general practitioner - Gańczak, Maria (Family Medicine & Primary Care Review, 2016)
In February 2016, the World Health Organization declared the Zika virus (ZIK V) a global health emergency due to the rapid spread of this infection. ZIK V has been responsible for major outbreaks in Africa and Asia, and between 2013–2015, in previously infection-naive territories of the Pacific area, South and Central America. Poland is not considered an endemic territory regarding ZIK V due to low temperatures which limit the survival of the Aedes mosquito. However, imported cases are possible due to numerous international travel made by Poles to countries in which ZIK V vectors are present. Three Zika cases imported from the endemic countries to Italy, the US and Japan are discussed in the article – together with epidemiology, modes of transmission, clinical manifestations of ZIK V disease and diagnostic options – in the context of possible cases imported to Poland. The role a GP should play in the detection of ZIK V infections and in the rapid response to potential threats is also stressed. ZIK V infection represents both clinical and diagnostic challenges for GPs and other specialists, due to similar symptoms to other arboviral diseases and cross-reaction with other flaviviruses, which could lead to misdiagnosis. For a Polish doctor, the current epidemiological situation and clinical manifestation should be the main criteria to suggest ZIK V infection. Despite establishing diagnosis and treatment of imported ZIK V infections, a GP should be prepared for sharing information with patients who will travel to areas of the vector activity (especially pregnant women and those planning to become pregnant in the near future, as well as their partners) about the necessity to take precautions during and after their journey.